Parameters affecting the period for being euthyroid in newly-diagnosed Graves’ disease treated with antithyroid agent - Ekinci, Iskender; Peynirci, Hande (International Journal of Research in Medical Sciences, 2020)
Background: There are limited data about the factors affecting the response time to medical treatment in Graves’ disease (GD) although many studies examined the predictors of the relapse after drug withdrawal. The aim of the current study was to evaluate the time for becoming euthyroid under antithyroid drug (ATD) therapy and the parameters influencing this period in patients diagnosed as GD. Methods: Patients with newly-diagnosed GD and decided to treat with ATD initially between March 2017 and September 2018 were retrieved retrospectively. Sociodemographic features as well as laboratory parameters like thyroid function tests and thyroid-stimulating hormone-receptor antibody (TRab) at the time of diagnosis were recorded. Results: Out of 41 patients, 63.4% (n=26) were female. The mean age was 36.1±11.7 years and 43.9% (n=18) of them were smoking. The time between the initiation of treatment and the duration of becoming euthyroid was 2.4±1.8 months. No significant difference was noted between age, gender, and smoking status and the time to become euthyroid under ATD treatment. This period was significantly positively correlated with levels of free triiodothyronine, free thyroxine, and negatively correlated with thyroid-stimulating hormone. Response to ATD therapy was higher in patients with pre-treatment TRab levels <10 IU/l than TRab ≥10 IU/l (p=0.011). Conclusions: Pretreatment thyroid function tests and TRab levels may be taken into consideration before deciding treatment in patients with newly diagnosed GD. It would be useful to design more comprehensive studies so that this proposal can find a response in clinical practice.